Effect of Porang Glucomannan Flour Formulation on the Characteristics of the Edible Coating Solution and The Quality of Manalagi Apples during Storage - Rusdianto, Andrew Setiawan; Amilia, Winda; Puspitania, Dewi Arum (International Journal on Food, Agriculture and Natural Resources, 2024)
Manalagi apples are an agricultural product that is easily damaged. Damage that occurs to Manalagi apples can be inhibited with an edible coating. The edible coating is a coating on the surface of fruit that can maintain quality and extend shelf life. Edible coatings can be made from hydrocolloids, including porang glucomannan. This research aims to determine the quality characteristics of Manalagi apples after being coated with an edible coating. Apart from that, to analyze the effect of glucomannan flour concentration on the quality characteristics of Manalagi apples, the viscosity of the edible coating solution, and the characteristics of the resulting coating and to choose the best treatment using the multiple attribute method. This research uses a Completely Randomized Design (RAL) with three replications. The treatment in this study was a glucomannan flour formulation of 5 levels, namely A0 (without treatment), A1 (0.5%), A2 (0.75%), A3 (1%), A4 (1.25%), carried out for storage for 7 days and observed on days 1, 3, 5, and 7 at room temperature (± 25℃). Porang glucomannan flour in edible coating significantly affected in respiration rate but had no significant effect on weight loss, L color, b color, and total dissolved solids. The best treatment based on calculation results using the multiple attribute method is A2 (0.75%) with the lowest weight loss was 2.97%, the highest L color with a value of 80, the lowest b color with a value of 15.1, the lowest total dissolved solids with a value of 11.6°Brix, the lowest respiration rate with a value of 0.006 ml CO2/gr/hour.